STRATEGI PEMASARAN UMKM YANG EFEKTIF DI ERA DIGITALISASI (Universitas Wijayakusuma Purwokerto, 2023)
The rapid development of technology in the digital era has made all activities carried out by the community online and instant. As a result, various types of businesses must compete in order to be glimpsed by potential customers, especially UMKM. Small or home business owners who are classified as UMKM must carefully plan UMKM strategies to advance their business. Keep in mind that today's business competition is getting tougher, so you have to be more careful in managing and marketing your business. The digital era is an era full of changes, for example how to communicate and how to transact. The presence of the internet has spurred people to choose methods that are fast, efficient and easy. This should be considered in the UMKM strategy. In this fast-paced era, UMKM businessmen must also act quickly in order to be able to excel when competing with competitors, ranging from fellow UMKM to corporations. The preparation of the UMKM strategy will certainly always follow all existing trends and developments so that business people must always be responsive to changes. Given the increasing number of UMKM (Micro, Small and Medium Enterprises) in Indonesia, this requires MSME owners to be more creative and innovative in developing effective marketing strategies for the development of UMKM